(untitled) (The Research of Medical Science Review, 2025)
Background: IV extravasation is the leakage of IV fluids into surrounding tissues leading to inflammation and possible long-term consequences. This problem is particularly serious with antibiotics. This study aims to evaluate nurses' knowledge about managing antibiotic-related IV extravasation and its association with demographic data. Objectives: To assess nurses' knowledge regarding the management of antibiotic-related IV extravasations and to examine the relationship between nurses' knowledge and demographic factors. Methodology: This was a cross-sectional descriptive study carried out among 208 nurses of HMC Peshawar. An adopted structured questionnaire was used to parallelly collect data on socio demographic characteristics, level of knowledge and practices. The sample size of 208 was based on a 95% confidence level, and the study measured convenience sampling in obtaining efficient data. Data were analyzed using SPSS, with chi-square and Pearson correlation to explore the relationship between demographic factors and knowledge and practices. Results: The findings of the study revealed notable gaps in the knowledge and practices of healthcare professionals regarding IV extravasation management. Among the participants, 49% demonstrated poor knowledge, and 45% displayed inadequate practices. The majority (75%) were aged 20–30 years, with 68% having less than five years of professional experience, and 73% were female. Participants with higher educational qualifications exhibited significantly better knowledge and practices, highlighting the importance of advanced training. These results emphasize the urgent need for targeted educational programs and standardized protocols to improve IV extravasation management and ensure patient safety. Conclusion: Inadequate education and training on IV extravasation management were found at HMC Peshawar. Enhancing nursing education through targeted training and updated curricula will improve patient safety and care.